Commercial activity, markets and entrepreneurs in the Middle Ages : essays in honour of Richard Britnell - Dodds, Ben; Liddy, Christian D. (Christian Drummond), 1973-; Britnell, R. H. (Boydell Press, 2011)
Long dominated by theories of causation involving class conflict and Malthusian crisis, the field of medieval economic history has been transformed in recent years by a better understanding of the process of commercialisation. In recognition of the important work in this area by Richard Britnell, this volume of essays brings together studies by historians from both sides of the Atlantic on fundamental aspects of the medieval commercial economy. From examinations of high wages, minimum wages and unemployment, through to innovative studies of consumption and supply, business fraud, economic regulation, small towns, the use of charters, and the role of shipmasters and peasants as entrepreneurs, this collection is essential reading for the student of the medieval economy. Contributors: John Hatcher, John Langdon, Derek Keene, John S. Lee, James Davis, Mark Bailey, Christine M. Newman, Peter L. Larson, Maryanne Kowaleski, Martha Carlin, James Masschaele, Christopher Dyer.